LABOR PROTECTION IMPROVE WORKING CONDITIONS, INCREASE EMPLOYEES’ PRODUCTIVITY, IMPLEMENTATION OF REST REGIME - Karimov, Bahodir Uktam o‘g‘li; Eshmuxamedov, L. M. (Educational Research in Universal Sciences, 2023)
In the article, labor protection improves working conditions, increases the productivity of workers, and implements a rest regime. Information is provided on the role of ensuring the creation of safe working conditions, its essence, increasing work productivity, reducing fatigue, creating healthy work activities, and preventing accidents in production.